2013
DOI: 10.1016/j.jaac.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatments for Depression on Comorbid Anxiety, Attentional, and Behavioral Symptoms in Adolescents With Selective Serotonin Reuptake Inhibitor–Resistant Depression

Abstract: Objective To assess the relative efficacy of antidepressant medication, alone and in combination with cognitive behavioral therapy (CBT), on comorbid symptoms of anxiety, attention, and disruptive behavior disorders in participants in the Treatment of Resistant Depression in Adolescents (TORDIA) trial. Method Adolescents with selective serotonin reuptake inhibitor (SSRI)–resistant depression (N = 334) were randomly assigned to a medication switch alone (to another SSRI or to venlafaxine) or to a medication s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…However, individuals who were treated to remission (i.e., loss of study entry anxiety diagnoses) were 5.26 times less likely to subsequently report suicidal behavior (preparatory acts or behavior communicating ideation, or aborted, interrupted, or actual attempt(s)), and those who were treatment responders (or remitters) were 3.48 times more likely to show consistently low rates of self-reported mood symptoms over several years of follow-up. Consistent with most depression and anxiety treatment studies (Barrett et al, 2001;Curry et al, 2011;Hilton et al, 2013;Silverman et al, 1999), type of acute treatment had no effect on later secondary outcomes. One explanation for the lack of a treatment type effect is that treatment, independent of type of treatment, has beneficial effects.…”
Section: Discussionsupporting
confidence: 63%
“…However, individuals who were treated to remission (i.e., loss of study entry anxiety diagnoses) were 5.26 times less likely to subsequently report suicidal behavior (preparatory acts or behavior communicating ideation, or aborted, interrupted, or actual attempt(s)), and those who were treatment responders (or remitters) were 3.48 times more likely to show consistently low rates of self-reported mood symptoms over several years of follow-up. Consistent with most depression and anxiety treatment studies (Barrett et al, 2001;Curry et al, 2011;Hilton et al, 2013;Silverman et al, 1999), type of acute treatment had no effect on later secondary outcomes. One explanation for the lack of a treatment type effect is that treatment, independent of type of treatment, has beneficial effects.…”
Section: Discussionsupporting
confidence: 63%
“…In the main IMPACT trial analysis (Goodyer et al, 2017b), significant decreases in anxiety, depression, obsessions-compulsions, and antisocial behavior were noted. Previous randomized controlled trials of psychotherapy for depression have also demonstrated improvements in comorbid symptom domains, including anxiety, attentiondeficit/hyperactivity disorder, and conduct problems (Asarnow et al, 2009;Hilton et al, 2013). Our results suggest that decreases in these various symptom domains can be best understood as overall decreases in psychopathology, rather than improvements in discrete symptom areas.…”
Section: Discussionsupporting
confidence: 55%
“…Evidence for this general factor runs counter to most current clinical practices, which often focus on categorical diagnosis and associated narrow-band questionnaires, and presumes disorder-specific interventions (Caspi & Moffitt, 2018;Hopwood et al, 2019;Messer & Wampold, 2006;Rodriguez-Seijas, Eaton, & Krueger, 2015). However, treatments often reduce symptoms in comorbid domains not explicitly targeted (Hilton et al, 2013;Weisz, McCarty, & Valeri, 2006), suggesting that interventions may decrease psychiatric symptoms overall, rather than those within a single category of psychopathology (Constantinou et al, 2019;Hopwood et al, 2019). We examined change in general and specific psychopathology factors among adolescents participating in psychosocial treatments for major depression in the IMPACT trial (Goodyer et al, 2017b(Goodyer et al, , 2011.…”
Section: Introductionmentioning
confidence: 92%
“…37 In the TORDIA study, remission from depression, regardless of treatment, was associated with a greater reduction in measures of anxiety, attention-deficit/hyperactivity disorder (ADHD), and oppositional symptoms. 38 Although the evidence is limited, treating depression in children/adolescents may reduce comorbid disorder(s) symptoms.…”
Section: Childhood and Adolescence: A Unique Neurodevelopmental Periodmentioning
confidence: 99%